MODEL PEMILIHAN SERENTAK DI INDONESIA - Muhammad Anwar Tanjung; Derita Prapti Rahayu; Putri Ade Tami (Jurnal Yudisial, 2021)
ABSTRAKKajian ini mengeksplorasi Putusan Mahkamah Konstitusi Nomor 55/PUU-XVII/2019 mengenai beberapa model dalam penyelenggaraan pemilihan umum dan pemilihan serentak di Indonesia. Fakta pemilu serentak lima kotak suara sebagai model penyelenggaraan pemilu serentak bukanlah satu-satunya gagasan yang berkembang dan diperdebatkan selama perubahan UUD NRI 1945. Putusan Mahkamah Konstitusi Nomor 55/PUU-XVII/2019 tentang Uji Materiil Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum terhadap UUD NRI 1945 telah memberikan pilihan model pemilihan serentak di Indonesia. Oleh sebab itu, rumusan masalah dalam kajian ini ialah bagaimana pertimbangan hakim dalam Putusan Mahkamah Konstitusi Nomor 55/PUU-XVII/2019 dapat menjadi landasan normatif yang mengarah kepada transformasi pemilihan di Indonesia. Penelitian ini menggunakan metode penelitian hukum normatif dengan menggunakan UUD NRI 1945 dan putusan hakim sebagai bahan hukum primer dan hasil penelitian terkait sebagai bahan hukum sekunder. Temuan penelitian ini menyimpulkan bahwa transformasi pemilihan di Indonesia dilakukan dengan memperhatikan batasan/defenisi rezim pemilu dan rezim pemilu daerah/lokal. Rezim pemilu berdasarkan UUD NRI 1945 yakni Pemilu Presiden dan Wakil Presiden, DPR, DPD dan DPRD. Rezim pemilihan daerah/lokal adalah pemilihan gubernur dan wakil gubernur dan bupati/wakil bupati maupun walikota/wakil walikota. Landasan normatif menuju transformasi pemilu dan model pemilihan di Indonesia dilakukan dengan penerapan e-rekap, penyederhanaan jumlah partai politik atau penggunaan proporsional tertutup, penataan ulang kelembagaan penyelenggara pemilu, model sosialisasi yang efektif, rekrutmen penyelenggara pemilu yang berintegritas, pengawasan dan penegakan hukum pemilu melalui khusus pemilu.Kata kunci: pemilu lima kotak; pemilihan serentak; peradilan khusus pemilu; uji materiil. ABSTRACTThis study explores the Constitutional Court Decision Number 55/PUU-XVII/2019 regarding several models in holding general elections and simultaneous elections in Indonesia. The fact that the simultaneous election of five ballot boxes as a model for simultaneous  elections is not the only idea that has developed and been debated during the amendment to the 1945 Constitution. The Constitutional Court Decision Number 55/PUU-XVII/2019 on the Judicial Review of Law Number 7 of 2017 concerning General Elections to the 1945 Constitution of the Republic of Indonesia has provided a choice of simultaneous election models in Indonesia. Therefore, the formulation of the problem in this study is how the judges’ considerations in the Constitutional Court Decision Number 55/PUUXVII/2019 can be a normative basis that leads to the transformation of elections in Indonesia. This study uses a normative legal method with the 1945 Constitution of the Republic of Indonesia and the judges’ decisions as primary legal sources and the relevant research results as secondary legal sources. From the results of this study, it can be concluded that the electoral transformation in Indonesia is carried out by taking into account the boundaries/ definitions of the electoral regime, and the regional/local election regime. The election regime is based on the 1945 Constitution of the Republic of Indonesia, which includes the elections for the President and Vice President, DPR, DPD and DPRD. Regional/local election regimes cover the election of governors and deputy governors and regents/deputy regents as well as mayors/deputy mayors. The normative basis for the transformation of elections and electoral models in Indonesia is carried out by implementing e-recap, simplifying the number of political parties or using closed proportional, reorganizing election management institutions, implementing effective socialization models, logistics management, recruitment of election organizers of integrity, supervision and law enforcement through a special election court.Keywords: election of five ballot boxes; simultaneous election; special election court; judicial review.